Private blog reflections connecting course content with field experiences: preservice teachers grapple with teacher identity. Issue 2 (4th March 2019) - Eutsler, Lauren; Curcio, Rachelle
ABSTRACT: A challenge experienced within teacher preparation programs is the ability to help preservice teachers connect educational theory with teaching practice. Guided by Dewey's phases of reflective thinking and Schön's reflection on action as an ethic for inquiry, we embedded a systematic reflection of written responses, recorded in a private weblog over the course of a 15-week intermediate reading methods course. Inductive thematic analysis of responses revealed the following themes: visceral thought, vulnerability, interpretation of course content, and identity formation toward becoming a classroom teacher. Our findings exemplify how systematic reflection in a private digital space contributed to the development of preservice teachers' professional identities.